IMPLEMENTASI PENGGUNAAN BAHAN AJAR BERBASIS MULTIMEDIA DALAM MENINGKATKAN PEMAHAMAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI 1 KEPENUHAN HULU - SARMADHAN LUBIS; ISKANDAR LUBIS (ABDUSSALAM : Jurnal Pendidikan Dan Kebudayaan Islam, 2026)
Islamic Religious Education (PAI) is a compulsory subject in junior high school and forms part of the curriculum. This subject is included in the curriculum of State Junior High School 1 Kepenuhan Hulu. The use of PAI learning materials, from the initial presentation to the conceptualization of ideas, has proven to be highly engaging for students. Moreover, the use of multimedia-based teaching materials can enhance students' understanding of the subject matter, thereby ensuring effective knowledge acquisition. This study aims to identify the challenges and solutions faced by Islamic religious education teachers in improving students’ learning comprehension through the implementation of multimedia-based teaching materials at State Junior High School 1 Kepenuhan Hulu. This research uses a qualitative approach, specifically selecting State Junior High School 1 Kepenuhan Hulu as the research site. Data sources were obtained from both primary and secondary data relevant to the research issues. This study aims to examine the implementation of multimedia-based teaching materials in improving students’ understanding of Islamic Religious Education subjects. The use of multimedia, which combines elements of text, images, audio, and video, is believed to create a more engaging and interactive learning experience. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results indicate that multimedia-based teaching materials can enhance students’ attention, interest, and comprehension of the subject matter. Furthermore, students become more active and enthusiastic during the learning process. Therefore, the application of multimedia in teaching materials proves to be effective in improving the quality of Islamic Religious Education learning.